Underpinnings of higher level motivational orientations - Skatova, Anna A. (2011)
This thesis explored underpinnings of the higher level motivational orientations, generic to various types of human choice, such as pro-social, intrinsic, achievement motivation and free-riding. Two different choice situations were examined: a choice of degree was utilized as a model of a real life choice and an experimental economic game (e.g. a public goods game) was used to study choices in a controlled laboratory environment. Reinforcement Sensitivity Theory (RST, Gray & McNaughton, 2000) was employed as a theoretical framework of biological motivational traits to examine their links to higher level motivational orientations. RST proposes that individual differences in a vast range of behaviours are linked to individual propensities to approach or avoid in rewarding or punishing contexts. Thus, an individual differences framework was applied to study underpinnings of higher level motivational orientations through their links to the basic motivational traits of behavioural approach and inhibition.